Diseño e implementación de un sistema fotovoltaico de generación eléctrica para vivienda sostenible de interés social del AEIRNNR. - Quinche Bravo, Jorge Vinicio (2012)
This project is done the calculation, design and implementation of a photovoltaic system to supply electricity to a sustainable housing of social interest, for which it has done an analysis of solar radiation in the city of Loja where monitoring is was made during a year, then researched on the conversion of solar energy into electricity using photovoltaic cells, then analyzes the performance of autonomous photovoltaic systems, components and recommendations to be taken into account for sizing and selection of equipment to use. According to data obtained from solar radiation and its geographical location (latitude), the city of Loja qualifies for the implementation of photovoltaic systems, which can provide electricity to remote communities interconnected electricity networks. We performed the collection of information content required for the development of this research is structured by the introduction, six chapters, conclusions and recommendations.